2022
DOI: 10.1186/s10195-022-00641-y
|View full text |Cite
|
Sign up to set email alerts
|

Remnant preservation may improve proprioception after anterior cruciate ligament reconstruction

Abstract: Aim Our aim was to evaluate the literature investigating proprioception improvement after anterior cruciate ligament reconstruction (ACLR) and test the hypothesis that ACL tibial remnant-preserving reconstruction (ACLR-R) is more beneficial than standard technique (ACLR-S) in terms of postoperative proprioceptive function with various reported tests, including joint position sense (JPS) and threshold to detect passive motion (TTDPM). Methods An onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…With the ASP technique, the medial tibial spine is covered by ACL fibers, which means that surgeons mainly reference ACL remnants and other landmarks such as the posterior border of the ARLM and PCL for tibial tunnel placement. 8,19,22 Additionally, the ASP technique has shown benefits in retaining proprioceptors on the synovium of residual ligamentous tissue, accelerating the recovery of neuromuscular control and knee function, 1,7 maintaining the stability of the knee joint and decreasing the mechanical load on the graft, 9,14,25 and hastening biological healing of the graft by enhancing cell proliferation and revascularization . [24][25][26]29 Moreover, owing to the presence of functional cells in the remnants, tunnel widening, which is thought to result from synovial fluid egress, can be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…With the ASP technique, the medial tibial spine is covered by ACL fibers, which means that surgeons mainly reference ACL remnants and other landmarks such as the posterior border of the ARLM and PCL for tibial tunnel placement. 8,19,22 Additionally, the ASP technique has shown benefits in retaining proprioceptors on the synovium of residual ligamentous tissue, accelerating the recovery of neuromuscular control and knee function, 1,7 maintaining the stability of the knee joint and decreasing the mechanical load on the graft, 9,14,25 and hastening biological healing of the graft by enhancing cell proliferation and revascularization . [24][25][26]29 Moreover, owing to the presence of functional cells in the remnants, tunnel widening, which is thought to result from synovial fluid egress, can be prevented.…”
Section: Discussionmentioning
confidence: 99%
“…c, d One year after the ACL reconstruction procedure, which used ADC as the landmark positioning femoral tunnel, the ACL was reconstructed without sacrificing the remnant, and there were no abnormal symptoms such as joint swelling and surrounding structural abnormalities [6,12,43]. The remnants that are truly worth preserving might be those that are "functional", and the criteria for "functional" remain to be explored [5,30]. Additionally, most of the studies on remnant-preserving ACLR have focussed on tibial remnants instead of femoral remnants since femoral remnants are usually small [38] and relatively rare [30].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, remnants of the ruptured ligament need to be removed properly to achieve accurate tunnel positioning in the NRP technique. However, RP may show certain benefits in terms of proprioceptive function [6], stability [14], and graft healing [31]. Takahashi et al reported that preserving ACL residues might enhance the synovial coverage of the grafted tendon and the outcome of graft healing without increasing cyclops lesions, and sufficient remnant tissue coverage might contribute to better knee stability [31].…”
Section: Discussionmentioning
confidence: 99%
“…Several landmarks have been used for anatomical femoral tunnel positioning, including the lateral intercondylar ridge, the lateral bifurcate ridge, and the cartilage margin [8, 17, 34], but it is often difficult to locate anatomical landmarks without sacrificing the remnant tissue both at the tibial and femoral sites. Remnant preservation (RP) has shown multiple advantages including preservation of the proprioceptive function [1, 6, 32], preservation of laxity [7], reduction of tunnel enlargement [7, 33], and promotion of graft healing [19]. During the implementation of the RP technique, surgeons generally refer to the location of remnants to centre the graft within the remnant tissue, though a foreshortened view must be used to judge the position inside a covered footprint.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation